MicroRNA profiling reveals novel biomarkers for cardiovascular and psychological health in plateau psycho CVD - Xiu-Long Niu; Guo-Qing Liang; Shao-Bo Chen; Yan Li; Tao Wang; Xiaojing Wang; Qing Guo; Dong Gu; Le Kang; Changxing Liu; Xun Bi; Wei Cai (Scientific Reports)
Abstract This study aimed to explore the expression characteristics of miRNAs in cardiovascular diseases (CVD) and depression within a plateau environment, to better understand their potential role in Plateau Psycho-CVD. A prospective study design was employed to analyze circulating small RNAs from 20 subjects using high-throughput sequencing technology. Participants were divided into four groups (C, PPC, PP, PC) for comparative analysis. Differentially expressed miRNAs were selected for further functional enrichment analysis. The findings revealed that hsa-miR-1976 and hsa-miR-4685-3p were significantly upregulated in patients with Plateau Psycho-CVD and mental health issues. These miRNAs were closely associated with key pathways relevant to cardiovascular and mental health, including the PI3K-Akt and neurotrophin signaling pathways. Additionally, the downregulated miRNAs in the PPC group were linked to increased expression of AKT1 and STAT3, genes associated with bipolar disorder and inflammatory pathways, indicating a potential impact on neural function. This study identifies hsa-miR-1976 and hsa-miR-4685-3p as novel biomarkers for plateau stress dual heart disease, with AKT1 and STAT3 emerging as potential therapeutic targets. These insights pave the way for further research and clinical applications in related fields.